Quinoidal Molecules as a New Class of Ambipolar Semiconductor Originating from Amphoteric Redox Behavior. (13th January 2015) - Hwang, Hansu; Khim, Dongyoon; Yun, Jin‐Mun; Jung, Eunhwan; Jang, Soo‐Young; Jang, Yun Hee; Noh, Yong‐Young; Kim, Dong‐Yu
Abstract : The two small molecules, quinoidal bithiophene (QBT) and quinoidal biselenophene (QBS), are designed based on a quinoid structure, and synthesized via a facile synthetic route. These quinoidal molecules have a reduced band gap and an amphoteric redox behavior, which is caused by an extended delocalization. Due to such properties, organic field‐effect transistors based on QBT and QBS have shown balanced ambipolar characteristics. After thermal annealing, the performances of the devices are enhanced by an increase in crystallinity. The field‐effect hole and electron mobilities are measured to be 0.031 cm 2 V −1 s −1 and 0.005 cm 2 V −1 s −1 for QBT, and 0.055 cm 2 V −1 s −1 and 0.021 cm 2 V −1 s −1 for QBS, respectively. In addition, we investigate the effect of chalcogen atoms (S and Se) on the molecular properties. The optical, electrochemical properties and electronic structures are mainly dominated by the quinoidal structure, whereas molecular properties are scarcely affected by either type of chalcogen atom. The main effect of the chalcogen atoms is ascribed to the difference of crystallinity. Due to a strong intermolecular interaction of the selenophene, QBS exhibits a higher degree of crystallinity, which leads to an enhancement of both hole and electron mobilities. Consequently, these types of quinoidal molecules are found to be promising for use as ambipolar semiconductors. Abstract : Quinoidal organic semiconductors containing dichalcogenophene (quinoidal bithiophene and quinoidal biselenophene) are designed and synthesized by facile synthetic route. Due to the extended delocalization of quinoid structure, they show low band gap and amphoteric redox behavior. Compared with common aromatic compounds, such unusual properties of quinoid structure give rise to balanced ambipolar charge transport in the top gate field‐effect transistor devices.